PELATIHAN DESIGN PRODUK UNTUK MENINGKATKAN KUALITAS BATIK ASLI SIDOARJO - Susi Ratnawati; Ahmad Hidayat (Jurnal Pengabdian Dharma Wacana, 2021)
Batik Sidoarjo has two regions that became the trademark of Sidoarjo batik, batik and batik Jetisan of Jetis Kenongo of Reinforcement. The difference they are located on the motifs, colors and history. Batik motif Jetisan has a classic and just a few modifications. As for the batik Kenongo is the work of designer prior to 2006 lapindo mud disaster befall Sidoarjo district, Sidoarjo batik craft centers visited by many cutomers from different areas. Sidoarjo batik is one tourist destination shopping in Sidoarjo, in addition to industrial centers and industrial bags and luggage thunderstorm Sidoarjo. But since the Lapindo mud disaster occurs, there is also a decrease of sales turnover by 60%. The fall in sales turnover also resulted in a decrease in revenue received craftsmen. In order to decrease turnover not there are some things that can be done by the craftsmen, among others: 1) Create a model of the design development of batik design innovative and varied, and original works of craftsmen, especially batik today's competition more rapidly, 2) select and define marketing strategies appropriate.